2005
DOI: 10.1111/j.1523-1755.2005.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination in human immunodeficiency virus-infected adults receiving hemodialysis

Abstract: Hepatitis B vaccination should be offered to all HIV-infected ESRD patients because over half of the patients with HIV and ESRD can develop protective antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Many clinical factors may be responsible for the lower seroconversion rate to recombinant hepatitis B vaccine in patients with CKD including older age [25], nutritional status [26], HIV infection [27], possession of the major histocompatibility complex haplotype HLA-B [28], and diabetes mellitus [29], among others. Controversial evidence exists about the effect of rHuEPO therapy on the outcome of the immune response to four doses of recombinant HBV vaccine in a CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical factors may be responsible for the lower seroconversion rate to recombinant hepatitis B vaccine in patients with CKD including older age [25], nutritional status [26], HIV infection [27], possession of the major histocompatibility complex haplotype HLA-B [28], and diabetes mellitus [29], among others. Controversial evidence exists about the effect of rHuEPO therapy on the outcome of the immune response to four doses of recombinant HBV vaccine in a CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is the uncertain generalizability given the relatively low hemoglobin levels of the patients. Of note, it has been suggested that higher hemoglobin levels may have favorable effects on hepatitis B vaccine immunogenicity [18,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, Sasaki et al [29] obtained a 72% response rate with a double-dose regimen (40 μg per dose) of ENGERIX-B ® , plus an adjuvant, Rh granulocyte-macrophage colony-stimulating factor (GM-CSF; Novartis Pharmaceuticals, Basel, Switzerland) [29]. A recent clinical trial in HIV-positive patients receiving hemodialysis demonstrated a 50% response rate to vaccine [30]. As HIV affects CD4+ cell count, cell function, and Th1/Th2 balance, the observed response rates to vaccine are not surprising.…”
Section: Vaccine Efficacy In Hiv-positive Patientsmentioning
confidence: 96%